Somatostatin-IRES-Cre Mice: Between Knockout and Wild-Type? - Viollet, Cécile; Simon, Axelle; Tolle, Virginie; Labarthe, Alexandra; Grouselle, Dominique; Loe-Mie, Yann; Simonneau, Michel; Martel, Guillaume; Epelbaum, Jacques (Frontiers in Endocrinology, 2017)
The neuropeptide somatostatin (SOM) is widely expressed in rodent brain and somatostatin-IRES-Cre (SOM-cre) mouse strains are increasingly used to unravel the physiology of SOM-containing neurons. However, while Knock-In targeting strategy greatly improves Cre-Lox system accuracy, recent reports have shown that genomic insertion of Cre construct per se can markedly affect physiological function. We show that Cre transgene insertion into the 3’UTR of the somatostatin gene leads to the selective and massive depletion of endogenous SOM in all tested brain regions. It also strongly impacts SOM-related neuroendocrine responses in a similar manner to what has been reported for SST KO mice : increased corticosterone levels after 30-min restraint stress, decreased amplitude and regularity of ultradian GH secretory patterns accompanied by changes in sexually dimorphic liver gene expression (serpina1, Cyp2b9, Cyp2a4, Cyp2d9 and Cyp7b1). In addition to demonstrating the need for examination of the consequences of Cre transgenesis, these results also reveal how this SOM-cre strain may be a useful tool in studying the functional consequences of moderate to low SOM levels as reported in neurological and psychiatric disorders.